2022
DOI: 10.1186/s12887-022-03484-y
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of splenic torsion in children: preoperative thrombocytosis predicts splenic infarction

Abstract: Background Pediatric splenic torsion is a rare entity, and the most common cause is wandering spleen. This study aimed to summarize our clinical experience in the diagnosis and surgical treatment pediatric patients with splenic torsion, and to use preoperative thrombocytosis as a preoperative predictive factor for splenic infarction. Methods From January 1st, 2016 to December 31st, 2021, 6 children diagnosed as splenic torsion were included. All pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Wang et al, in their case series, suggested the role of preoperative thrombocytosis as a predictor of splenic infarction. 10 A similar scenario was seen in our study also, where thrombocytosis was associated with splenic infarction. It is too premature to say that; thrombocytosis is a marker of splenic infarction.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Wang et al, in their case series, suggested the role of preoperative thrombocytosis as a predictor of splenic infarction. 10 A similar scenario was seen in our study also, where thrombocytosis was associated with splenic infarction. It is too premature to say that; thrombocytosis is a marker of splenic infarction.…”
Section: Discussionsupporting
confidence: 89%
“…7 Wang et al also suggested that early abdominal cross-sectional contrast imaging (especially contrast CT) should be performed to make an early and correct diagnosis, especially in children with abdominal pain and abdominal mass. 10 Another rarely used modality for the acute abdomen is magnetic resonance imaging which may show splenic infarction as peripheral wedgeshaped defects exhibiting reduced signal intensity on both T1-and T2-weighted images without contrast enhancement. 11 The degree of torsion, according to literature, ranges from 90° to 3600 o .…”
Section: Discussionmentioning
confidence: 99%
“…Involution or atrophy are the natural advancements of an infarcted accessory spleen [21]. Early diagnosis and timely surgical intervention are important in order to preserve the spleen [40]. It is essential to address any modifiable risk factors and monitor the patient for possible symptoms, conducting regular follow-ups to detect early signs of complications.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical intervention and conservative management are the two main splenic torsion treatment options. Splenectomy is the main choice of treatment for splenic torsion, but the spleen can also be preserved using detorsion, splenopexy, and an autotransplant [ 21 ]. More than 50% of patients who chose conservative management require subsequent surgery.…”
Section: Discussionmentioning
confidence: 99%